Strategi Pemasaran Perpustakaan Sekolah dalam Membangun Citra Positif Lembaga Pendidikan di SMP BP Daarussholah Sangatta Selatan - Juliana; Ramdanil Mubarok; Ismail Rahmat (BEduManagers Journal : Borneo Educational Management and Research Journal, 2026)
This study aims to analyze the marketing strategy of the school library in building a positive image of educational institutions and to identify its supporting and inhibiting factors at SMP BP Daarussholah Sangatta Selatan. This research employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation involving the Head of Library and the Vice Principal for Curriculum. Data analysis used the interactive model of Miles, Huberman, and Saldana, including data condensation, data display, and conclusion drawing. The findings indicate that the library marketing strategy was implemented through the Literacy Friday program, integration with learning activities, student motivation, and reward systems. Supporting factors include school policies, BOS funding, literacy programs, external cooperation, and positive student responses. Meanwhile, inhibiting factors consist of limited facilities and infrastructure, inadequate book collections, low reading interest influenced by technology, and budget constraints. The strategy has contributed positively to the school's image but still requires a more systematic and integrated development.